+0  
 
0
382
3
avatar

Suppose that for some a,b,c we have a+b+c = 6, ab + ac + bc = 5, and abc = -12. What is a^3 + b^3 + c^3?

Guest Jun 19, 2017

Best Answer 

 #3
avatar+19990 
+1

Suppose that for some a,b,c we have

a+b+c = 6,

ab + ac + bc = 5, and

abc = -12.

What is a^3 + b^3 + c^3?

 

1. 

\(\small{ \begin{array}{|rcll|} \hline (a+b+c)\times (ab + ac + bc) &=& 6\cdot 5 \\ (a+b+c)\times (ab + ac + bc) &=& 30 \\ a^2b+a^2c+abc+ab^2+abc+b^2c+abc+ac^2+bc^2 &=& 30 \\ a^2(b+c) +b^2(a+c) +c^2(a+b)+ 3abc &=& 30 \\ a^2(b+c) +b^2(a+c) +c^2(a+b) &=& 30 - 3abc \quad & | \quad abc = -12 \\ a^2(b+c) +b^2(a+c) +c^2(a+b) &=& 30 - 3(-12) \\ a^2(b+c) +b^2(a+c) +c^2(a+b) &=& 30 +36 \\ \mathbf{a^2(b+c) +b^2(a+c) +c^2(a+b)} & \mathbf{=} &\mathbf{66} \\ \hline \end{array} }\)

 

2.

\(\small{ \begin{array}{|rcll|} \hline (a+b+c)^3 &=& (a+b+c)^2\times (a+b+c) \\ 6^3 &=& \Big(a^2+b^2+c^2+2(ab + ac + bc ) \Big)\times (a+b+c) \quad | \quad ab + ac + bc = 5 \\ 216 &=& (a^2+b^2+c^2+2\cdot 5 )\times (a+b+c) \\ 216 &=&(a^2+b^2+c^2+10 )\times (a+b+c) \\ 216 &=&a^3+a^2(b+c)+b^3+b^2(a+c)+c^3+c^2(a+b)+10(a+b+c) \\ 216 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)+10(a+b+c) \quad | \quad a+b+c = 6\\ 216 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)+10\cdot 6\\ 216 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)+60 \\ 216-60 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)\\ 156 &=&a^3+b^3+c^3+\underbrace{a^2(b+c)+b^2(a+c)+c^2(a+b)}_{=66} \\ 156 &=&a^3+b^3+c^3+66 \\ 156-66 &=&a^3+b^3+c^3 \\ 90 &=&a^3+b^3+c^3 \\ \mathbf{a^3+b^3+c^3} & \mathbf{=} &\mathbf{90} \\ \hline \end{array} }\)

 

laugh

heureka  Jun 20, 2017
 #1
avatar
0

Solve for a, b, c

a = -1, a =3, a = 4

b = -1, b =3, b = 4

c = -1, c =3, c = 4

You can the values that balance your equations and cube them to get what you want.

Guest Jun 19, 2017
 #2
avatar+88775 
+1

 

 

a + b + c = 6 →  b + c  = 6 - a     (1)

ac + ab + bc  = 5  →  a ( b + c)  =  5 - bc     (2)

abc  = -12   →  bc = -12/a      (3)

 

Put (1)  and (3)  into (2)

 

a ( 6 - a) =  5 - (-12/a)

 

6a - a^2 =  5 + 12/a       multiply through by a

 

6a^2 - a^3  =  5a +  12      rearrange as

 

a^3 - 6a^2 +  5a +  12   =  0

 

Using the Rational Zeroes  Theorem, 3  is shown to be a root

 

Using synthetic division, we can find the remaining polynomial

 

 

3  [   1      -  6      5       12 ]

                   3    - 9      -12

       _________________

       1       - 3      -4       0

 

The remaining polynomial   is

 

a^2  - 3a  - 4

 

The zeroes of this are

 

(a - 4) (a + 1)  = 0    

 

4   and   -1

 

So...."a"  can arbitrarily  be either  3, 4  or -1

 

If we assign  "a" as  4,  "b"  and  "c"  can  be assigned as 4  and -1  respectively

 

And   a^3  +  b^3  + c^3  =    3^3 + 4^3 + (-1)^3  =  27 + 64 - 1  =  90

 

 

 

cool cool cool

CPhill  Jun 19, 2017
 #3
avatar+19990 
+1
Best Answer

Suppose that for some a,b,c we have

a+b+c = 6,

ab + ac + bc = 5, and

abc = -12.

What is a^3 + b^3 + c^3?

 

1. 

\(\small{ \begin{array}{|rcll|} \hline (a+b+c)\times (ab + ac + bc) &=& 6\cdot 5 \\ (a+b+c)\times (ab + ac + bc) &=& 30 \\ a^2b+a^2c+abc+ab^2+abc+b^2c+abc+ac^2+bc^2 &=& 30 \\ a^2(b+c) +b^2(a+c) +c^2(a+b)+ 3abc &=& 30 \\ a^2(b+c) +b^2(a+c) +c^2(a+b) &=& 30 - 3abc \quad & | \quad abc = -12 \\ a^2(b+c) +b^2(a+c) +c^2(a+b) &=& 30 - 3(-12) \\ a^2(b+c) +b^2(a+c) +c^2(a+b) &=& 30 +36 \\ \mathbf{a^2(b+c) +b^2(a+c) +c^2(a+b)} & \mathbf{=} &\mathbf{66} \\ \hline \end{array} }\)

 

2.

\(\small{ \begin{array}{|rcll|} \hline (a+b+c)^3 &=& (a+b+c)^2\times (a+b+c) \\ 6^3 &=& \Big(a^2+b^2+c^2+2(ab + ac + bc ) \Big)\times (a+b+c) \quad | \quad ab + ac + bc = 5 \\ 216 &=& (a^2+b^2+c^2+2\cdot 5 )\times (a+b+c) \\ 216 &=&(a^2+b^2+c^2+10 )\times (a+b+c) \\ 216 &=&a^3+a^2(b+c)+b^3+b^2(a+c)+c^3+c^2(a+b)+10(a+b+c) \\ 216 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)+10(a+b+c) \quad | \quad a+b+c = 6\\ 216 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)+10\cdot 6\\ 216 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)+60 \\ 216-60 &=&a^3+b^3+c^3+a^2(b+c)+b^2(a+c)+c^2(a+b)\\ 156 &=&a^3+b^3+c^3+\underbrace{a^2(b+c)+b^2(a+c)+c^2(a+b)}_{=66} \\ 156 &=&a^3+b^3+c^3+66 \\ 156-66 &=&a^3+b^3+c^3 \\ 90 &=&a^3+b^3+c^3 \\ \mathbf{a^3+b^3+c^3} & \mathbf{=} &\mathbf{90} \\ \hline \end{array} }\)

 

laugh

heureka  Jun 20, 2017

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.